Shifting Neoliberalism in US Telecommunications Policy: A Critical Reading of Chicago School Roads - Sydney L Forde (tripleC: Communication, Capitalism & Critique, 2024)
Popular narratives characterising neoliberal economic orthodoxy hold that all forms of government intervention are counter-productive to free markets. Conservatives who claim to embody such liberalism often trace opposition to government interventions to two founding Chicago School economists, Friedrich August von Hayek and Milton Friedman. Through close examinations of the seminal works from Hayek and Friedman, this paper complicates the relationship between the “free-market” neoliberal economic imaginaries derived from both economists’ seminal books as “utopian neoliberalism”, and modern commercial-focused telecommunications policies premised on the active construction of industry serving conditions as “political neoliberalism”. In examining the CONNECT Act aimed at banning the municipal deployment of broadband services in every state across America, this analysis demonstrates significant differences between “utopian” and “political” articulations of neoliberalism, with the latter appearing to ground language and justifications in the former, while simultaneously contradicting baseline principles of such. The seemingly baseless motivations behind the contradictory logics of political neoliberalism are critically assessed and the role of corporate domination of the US telecommunications sector as a guiding philosophy for neoliberal policymakers is discussed.